2022
DOI: 10.1210/clinem/dgac190
|View full text |Cite|
|
Sign up to set email alerts
|

Serum Uric Acid Levels and Nonalcoholic Fatty Liver Disease: A 2-Sample Bidirectional Mendelian Randomization Study

Abstract: Background Observational studies have shown that non-alcoholic fatty liver disease (NAFLD) is highly correlated with serum uric acid (SUA). However, these studies have an inherent risk of bias due to reverse causality. Here, we perform a Mendelian randomization (MR) study to investigate causality between SUA and NAFLD. Methods We performed a two-sample bidirectional MR analysis using summary-level data from genome-wide associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
6
2
Order By: Relevance
“…Furthermore, SUA levels are associated with the development of cirrhosis after adjustments for risk factors for chronic liver disease in a US nationwide cohort, 7 which was similar to the present findings for SLD. However, an MR study restricted to individuals of European ancestry does not confirm a causal association between SUA levels and the risk of NAFLD 18 . Correspondingly, causality was not discovered in the present study.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, SUA levels are associated with the development of cirrhosis after adjustments for risk factors for chronic liver disease in a US nationwide cohort, 7 which was similar to the present findings for SLD. However, an MR study restricted to individuals of European ancestry does not confirm a causal association between SUA levels and the risk of NAFLD 18 . Correspondingly, causality was not discovered in the present study.…”
Section: Discussioncontrasting
confidence: 92%
“…However, an MR study restricted to individuals of European ancestry does not confirm a causal association between SUA levels and the risk of NAFLD. 18 Correspondingly, causality was not discovered in the present study. The discrepancy between cohort studies and MR analyses may be because of the magnitude of exposure determined by genetic instruments not being equal to the exposure in observational studies, which generally leads to a null association in MR analysis.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Our findings are consistent with those of previous studies showing that serum uric acid levels were significantly associated with NAFLD prevalence. 24,25 A study based on the NHANES 1988-1994 in the United States also identified similar results between elevated uric acid level and ultrasound-diagnosed NAFLD in non-diabetic adults. 26 However, the effect of kidney function on the sUA level has been neglected in many studies, and sUA/Cr, a renal function-normalized index, might be a better biomarker.…”
Section: Discussionmentioning
confidence: 78%
“…Some MR studies have been performed to explore the relationship between exposure and NAFLD. However, the main focus was single exposures or common exposure factors, such as interleukin-6 (IL-6) ( Li et al, 2022a ), seven sleep characteristics ( Fan et al, 2022 ), serum uric acid levels ( Li et al, 2022b ), iron status ( He et al, 2022 ), and coronary artery disease ( Ren et al, 2022 ). Few studies have focused on blood metabolites and NAFLD.…”
Section: Introductionmentioning
confidence: 99%